The effects of digital inclusion and ICT access on the quality of life: A global perspective - Alhassan, Muftawu Dzang; Adam, Ibrahim Osman (Technology in society, 2021)
The role of Information Communication Technologies (ICTs) on the quality of life (QoL) has garnered much research interest recently given the pervasiveness of ICTs in our daily lives. However, whilst the evidence on the effects of ICTs in improving QoL at the individual country level is mixed, the evidence at the global level has not also been fully understood. Besides, the evidence on the linkages between ICTs, digital inclusion, and QoL has been underexplored in information systems research. Even though existing empirical research has largely provided specific results using single country data, there remains a gap in our understanding of the dual effects of digital inclusion and ICT access on QoL and the mediating role of ICT usage at the global level. This study seeks to address these by relying on secondary data from 121 countries for 2018 and structuration theory as a theoretical lens. The results from our PLS-SEM analysis show that digital inclusion and ICT access significantly influence QoL at the global level. Furthermore, our results show support for the mediating effects of ICT usage on the linkages between digital inclusion and QoL. The findings from this study provide key insights that explain how QoL may be enhanced through ICTs. •This study examines the effect of digital inclusion and ICT access on Quality of Life (QoL) at the global level.•Using PLS-SEM, our results reveal that digital inclusion and ICT access significantly influences QoL at the global.•Our results further show support for the mediating effects of ICT usage on the linkages between digital inclusion and QoL. The mediating effects of ICT usage on the relationship between ICT access and QoL was however not supported.•The mediating effects of ICT usageon the relationship between ICT access and QoL was however not supported.•Digital inclusion through access to affordable ICTs can enhance people’s capability and promote their QoL.